Computational chemical analysis of unconjugated bilirubin anions and insights into pKa values clarification - Vega Hissi, Esteban Gabriel (2013)
The pKa, the negative logarithm of the acid dissociation equilibrium constant, of the carboxylic acid groups of unconjugated bilirubin in water is a discussed issue because there are quite different experimental values reported. Using quantum mechanical calculations we have studied the conformational behavior of unconjugated bilirubin species (in gas phase and in solution modeled implicitly and explicitly) to provide evidence that may clarify pKa values because of its pathophysiological relevance. Our results show that rotation of carboxylate group, which is not restricted, settles it in a suitable place to establish stronger interactions that stabilizes the monoanion and the dianion to be properly solvated, demonstrating that the rationalization used to justify the high pKa values of unconjugated bilirubin is inappropriate. Furthermore, low unconjugated bilirubin (UCB) pKa values were estimated from a linear regression analysis.